Valuing feedback: an evaluation of a National Health Service programme to support compassionate care practice through hearing and responding to feedback. (March 2017) - Smith, S; Gentleman, M; Conway, Linda; Sloan, Sue
There is an emergent recognition in healthcare that people need to be at the heart of services, and experiences of care matter; these should therefore be recognised and enhance practice. The aims of this research were to evaluate an NHS development programme, Valuing Feedback. The programme focused on supporting compassionate care practice by enabling NHS staff to listen, learn and respond to feedback enabling the development of practice. Findings identified that participants had a heightened awareness of the power and importance of feedback to support practice change. An enhanced understanding of using the feedback tools, Emotional Touchpoints and Envision Cards, was evident and working with these tools during the programme supported local implementation. Participants identified learning and changes to their practice resulting from feedback, specifically development in their own practice and service change. Participants identified that listening to positive and negative feedback based on emotional experience involved being brave. There was a requirement to be open and listen to criticism. Participants highlighted that feedback activities require support, as they need time to plan, undertake, reflect upon and initiate development. Conclusions from this research highlight the value of feedback focused on emotions and understanding experiences of patients, relatives and staff. Such feedback impacted on practice. Opportunities where NHS staff shared and learned from feedback were highly valued. It is necessary to consider how the activity of feedback can be effectively supported, enabling staff, their teams and organisations to prioritise feedback activity and develop compassionate care practice for patients, relatives and staff.